Micro1278 Leads to Tumor Growth Arrest, Enhanced Sensitivity to Oxaliplatin and Vitamin D and Inhibits Metastasis via KIF5B, CYP24A1, and BTG2, Respectively - Lin, Weidong; Zou, Heng; Mo, Jinggang; Jin, Chong; Jiang, Hao; Yu, Chengyang; Jiang, Zufu; Yang, Yusha; He, Bin; Wang, Kunpeng (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is the most common cancer type in the digestive tract. Chemotherapy drugs, such as oxaliplatin, are frequently administered to CRC patients diagnosed with advanced or metastatic disease. A better understanding of the molecular mechanism underlying CRC tumorigenesis and the identification of optimal biomarkers for assessing chemotherapy sensitivity are essential for the treatment of CRC. Various microRNAs, constituting class of noncoding RNAs with 20-22 nucleotides, have served as oncogenes or tumor suppressors in CRC. We analyzed miR-1278 expression in clinical samples by qRT-PCR. We then explored the role of miR-1278 in CRC growth in vitro and in vivo as well as sensitivity to oxaliplatin via RNA-seq and gain- and loss-of-function assays. We found that miR-1278 was downregulated in CRC samples, correlating with advanced clinical stage, and overexpression of miR-1278 led to tumor growth arrest and increased sensitivity to oxaliplatin via enhanced apoptosis and DNA damage. Suppression of KIF5B by miR-1278 through direct binding to its 3’UTR was the mechanism for the miR-1278-mediated effects in CRC, miR-1278 inhibits metastasis of CRC through upregulation of BTG2. Additionally, we also found that the expression of CYP24A1, the main enzyme determining the biological half-life of calcitriol, was significantly inhibited by miR-1278, according to data from clinical, RNA-seq and functional assays, which allowed miR-1278 to sensitize CRC cells to vitamin D. In summary, our data demonstrated that miR-1278 may serve as a potential tumor suppressor gene and biomarker for determining sensitivity to oxaliplatin and vitamin D in CRC.